In vitro development of sugarcane seedlings using ethephon or gibberellin - Mendes, Luciane de Siqueira; Carvalho, Marcia Eugenia Amaral; Macedo, Willian Rodrigues; Castro, Paulo Roberto de Camargo e (Federal University of Piauí, 2018)
The use of plant growth regulators is directly related to the success of in vitro propagation, which is an advantageous alternative to obtain seedlings on a commercial scale. This study aimed to evaluate the in vitro development of ‘IAC 95-5000’ sugarcane seedlings after the addition of different doses of ethephon (0, 25, 50, 100 and 200 mg L-1) or gibberellic acid (0, 2.5, 5.0, 7.5 and 10.0 mg L-1) to the culture medium. Ethephon increased the number of tillers (up to 231.70%), reduced height of the main tiller (44.66 to 60.47%), and did not affect the shoot´s fresh and dry mass. On the other hand, gibberellin decreased the number of tillers and negatively changed biomass partitioning. It is concluded that the use of ethephon is a potential strategy to enhance in vitro production of ‘IAC 95-5000’ sugarcane seedlings, since it increased the number of usable shoots in subsequent subcultures, and its effects on height reduction can be reversible. However, the use of the tested doses of gibberellic acid is not recommended, because it impaired seedling development of this sugarcane variety.